Morphohistometric analysis of the effects of Coriandrum sativum on cortical and cerebellar neurotoxicity - Hesham N. Mustafa (Mashhad University of Medical Sciences, 2021)
Objective: Natural compounds can act as metal chelators and oxygen free radical scavengers, which allows them to be used as bioactive antagonists to heavy metals neurotoxicity. The aim of the study to analyze the morphometric effects of Coriandrum sativum (C. sativum) on lead-induced neurotoxicity.Materials and Methods: Forty Sprague-Dawley albino rats were divided into four equal groups (ten in each group): control group; coriander group: received aqueous C. sativum extracts (600 mg/kg BW for 60 days orally); lead (Pb) group: received a daily dose of lead acetate (Pb) (10 mg/kg BW for 60 days orally); Pb+ coriandrum group: received: aqueous C. sativum extract (600 mg/kg BW) prior to 10 mg/kg BW of Pb. The following parameters malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) were measured. Layers thickness and nuclei density were analyzed.Results: Lead levels in blood and tissues were decreased significantly in the Pb group and those findings were corrected significantly (p=0.001) with C. sativum addition. Data exhibited an increase in oxidative stress marker MDA and a decrease in antioxidant enzymes activities (SOD, CAT, and GPx) significantly in the Pb group and those effects were reversed significantly (p=0.001) by C. sativum administration. The cerebellar cortex and all layers of the somatosensory cortex thickness and nuclei density were diminished significantly in the Pb group. The morphometrical measurements were corrected significantly (p=0.001) by C. sativum.Conclusion: From the findings of the current study, Pb caused noticeable structural and functional variations in the cerebellar cortex and somatosensory cortex. C. sativum corrected these parameters as it possesses chelating and antioxidant potentials.